A new flavonoid glycoside from Elsholtzia bodinieri. Issue 20 (17th October 2016) - Zhong, Jin-Dong; Feng, Yue; Li, Hong-Mei; Xia, Xue-Shan; Li, Rong-Tao
Abstract: A new flavonoid glycoside, eriodictyol 7- O -(6″-caffeoyl)- β - D -glucopyranoside (1 ), along with 14 known compounds, were isolated from the whole plants of Elsholtzia bodinieri . All of the structures were determined by spectroscopic methods and chemical transformation. Compound1 and luteolin (9 ) exhibited potent anti-HCV activities with a selective index of 135.85 and 20.84, respectively. Abstract :